2012
DOI: 10.1186/1476-4598-11-59
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of cytotoxicity induced by Hsp90-targeted Antp-TPR hybrid peptide in glioblastoma cells

Abstract: BackgroundHeat-shock protein 90 (Hsp90) is vital to cell survival under conditions of stress, and binds client proteins to assist in protein stabilization, translocation of polypeptides across cell membranes, and recovery of proteins from aggregates. Therefore, Hsp90 has emerged as an important target for the treatment of cancer. We previously reported that novel Antp-TPR hybrid peptide, which can inhibit the interaction of Hsp90 with the TPR2A domain of Hop, induces selective cytotoxic activity to discriminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 41 publications
4
32
0
Order By: Relevance
“…AAG is an anti-tumour drug that inhibits the activity of Hsp90, a protein necessary for the growth of the cells [62,63]. The cytotoxicity results showed that CdSe(S) QDs inhibit the cell viability by 64.4±0.5% at a concentration of 500 µg/ml; a similar value to that of 17-AAG (66.4±2.7%) at a concentration of only 0.06 µg/ml ( Figure 5).…”
Section: Relative Toxicity Of Cdse(s) Qds In Comparison To 17-aag: Hssupporting
confidence: 62%
See 1 more Smart Citation
“…AAG is an anti-tumour drug that inhibits the activity of Hsp90, a protein necessary for the growth of the cells [62,63]. The cytotoxicity results showed that CdSe(S) QDs inhibit the cell viability by 64.4±0.5% at a concentration of 500 µg/ml; a similar value to that of 17-AAG (66.4±2.7%) at a concentration of only 0.06 µg/ml ( Figure 5).…”
Section: Relative Toxicity Of Cdse(s) Qds In Comparison To 17-aag: Hssupporting
confidence: 62%
“…In addition, 50% of cancer cells, including HCT-116, depend upon a heat-shock protein (such as Hsp90) to survive [61]. The viability of these cancer cells decreases in the presence of Hsp90 inhibitor 17-AAG, which is a common antitumour compound [62,63]. The viability of HCT-116 cells was therefore investigated both in the presence of 17-AAG and after treatment of the cells with QDs.…”
Section: Cytotoxicity Assaysmentioning
confidence: 99%
“…Therefore, it is likely that many of the activities of Hop in cancer are linked to perturbations in the function of the Hsp70/Hsp90 complex. This conclusion is supported by the observations that compounds that disrupt interactions between Hop and the Hsp90 or Hsp70 chaperone are toxic to cancer cells (Horibe et al 2011;Horibe et al 2012).…”
Section: Cancer Cell Biologysupporting
confidence: 53%
“…A hybrid peptide comprising a sequence based on the TPR2A region of Hop was designed to competitively inhibit the interaction between Hsp90 and Hop (Horibe et al 2011). This peptide induced cell death in a range of cancer cell lines in vitro, as well as displaying anti-tumour activity in a pancreatic cancer xenograft model (Horibe et al 2012). The compound also showed differential toxicity in that it did not affect the viability of normal cells, which might be attributed to the constitutive formation of the Hsp90 complex in cancer cells as opposed to normal cells (Barrott and Haystead 2013;Jego et al 2013).…”
Section: Cancer Cell Biologymentioning
confidence: 99%
“…20,21,24 Furthermore, it has also been shown that specific inhibitors 32 or a competitor peptide for the Hsp90-HOP 33 interaction inhibit tumor development, pointing to the Hsp90-HOP complex as a potentially selective anticancer therapeutic target. 33,34 Mechanistically, secreted HOP 35 carried by exosome-like extracellular vesicles 11 may promote PrP C -dependent proliferation via activation of PI3K and ERK1/2 7 or by binding to activin A receptor, type II-like kinase-2 and activating the SMAD-ID signaling. 26 Remarkably, our results demonstrate that PrP C is expressed in U87 cells and that its knockdown decreases proliferation in xenografted tumors and increases animal survival.…”
Section: Discussionmentioning
confidence: 99%